A purinergic call to arms from dying brown adipocytes - Mohammed K. Hankir (Cell Stress, 2022)
Brown adipocytes react to temperature and nutritional challenges by ramping up their metabolism and generating heat. This adaptation to changes in the environment is crucial for defending organismal homeostasis, but is impaired in obesity and during aging. Writing in Nature, Niemann et al. show that brown adipocytes become apoptotic under thermoneutral conditions and release ATP, which in turn is converted extracellularly into inosine. They further present evidence that pharmacological and genetic manipulations that enhance signalling of this purine metabolite stimulates thermogenesis in brown adipocytes and promotes metabolic health.